Economics of Horizontal Integration in Poultry Industry in South-West Nigeria - Moses , Bamiro, Olasunkanmi; Olanrewaju, Otunaiya, Abiodun; Olubanjo, Idowu, Adewunmi (International Journal of Poultry Science, 2011)
The broad objective of this study is to analyze the economics of horizontal integration in poultry production in some selected local government areas in south-west, Nigeria. Data was collected from 61 fish farmers, 40 poultry farmers and 53 integrated fish and poultry farms, making a sample size of 154 farmers using purposive-snowball sampling process. Descriptive statistics, gross margin analysis and stochastic cost frontier were employed for data analysis. Analysis of socio-economic characteristics shows that most of the farmers in the study area are males, young within the age range of 30-